24. CURRENT SITUATION AND FACTORS RELATED TO HEPATITIS C VIRUS INFECTION IN PATIENTS ON METHADONE TREATMENT IN HA LONG CITY IN 2022 (Vietnam Journal of Community Medicine, 2025)
The objective of the study is to describe the current situation and some factors related to hepatitis C virus infection in patients receiving methadone treatment at the methadone treatment facility - Ha Long City Medical Center. Cross-sectional descriptive study on 384 patients treated with Methadone in Ha Long city. The rate of patients ever infected with hepatitis C virus before opioid addiction replacement treatment with methadone was 77.9%. Research results show that the group of patients with a high rate of HCV infection is related to the following factors: education level, duration of Metahdone treatment, having ever shared a needle, and ever having sex with a woman. The difference is statistically significant, with p < 0.05. People with high HCV infection rates have no difference with the following factors: marital status, HIV status and condom use. last sexual intercourse.
Keywords: Methadone; hepatitis C; Ha Long